PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PADA STARBUCK WISMA METROPOLITAN BUILDING - Surya Ningrum; Priyanto (LPPM Universitas Asa Indonesia, 2015)
Purpose- of this research is to find out how motivation could affect staff's performances. The hypothesis based on statement above is that the staff's overal performance could be affected by variable motivation. Design/methology/approach- Research conducted on starbuck wisma metropolitan building with a number of staff of 30. The method that are being used is descriptive method, historical method and documentation method. statistic method is for analyzing incoming data is a simple regression, heteroscedasticity test and coefficient correlation Findings- Based on the identification of problems and research framework, the research results are formulated as employee motivation as reflected by the dimensions of motives, expectations, and incentives affect the quality of employee performance and higher employee motivation as reflected by the dimensions of motives, expectations, and incentives, the higher also the quality of the performance, as reflected by the dimensions of speed, accuracy, and promptness. Research limitations- The total of respondent is limited, yet at the single company as object of research. Practical implications- direct financial rewards is preferable to be given by management to increase motivation and performance of the emloyeess as the output.